1996
DOI: 10.1182/blood.v88.9.3407.bloodjournal8893407
|View full text |Cite
|
Sign up to set email alerts
|

High-dose multidrug resistance in primary human hematopoietic progenitor cells transduced with optimized retroviral vectors

Abstract: Retroviral transfer of the multidrug-resistance 1 (mdr1) cDNA into primary human hematopoietic progenitor cells (HPC) of cancer patients undergoing high-dose chemotherapy has been proposed to protect the bone marrow from the dose-limiting cytotoxicity of cytostatic agents. Preclinical studies performed with vectors derived from the Moloney murine leukemia virus (MoMuLV) or the related Harvey murine sarcoma virus have established that chemoprotection of HPC is feasible. The efficacy of vector-mediated multidrug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…37,38 By comparing the frequency of drug-resistant GM-CFC and Rh123-effluxing myeloid cells with the results of the quantitative PCR, evidence for high expression of MDR1 in at least a third of the transduced cells was observed. Using SF1m or a similar vector, SF-MDR, comparable results were obtained in primary human hematopoietic cells, 27 even after xenotransplantation and in vivo differentiation in NOD/SCID-mice. 28 An even higher rate of cells expressing MDR1 to high levels can be achieved by further improvements of the vector technology, such as elimination of cryptic splice signals 39 and improvement of untranslated sequences.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…37,38 By comparing the frequency of drug-resistant GM-CFC and Rh123-effluxing myeloid cells with the results of the quantitative PCR, evidence for high expression of MDR1 in at least a third of the transduced cells was observed. Using SF1m or a similar vector, SF-MDR, comparable results were obtained in primary human hematopoietic cells, 27 even after xenotransplantation and in vivo differentiation in NOD/SCID-mice. 28 An even higher rate of cells expressing MDR1 to high levels can be achieved by further improvements of the vector technology, such as elimination of cryptic splice signals 39 and improvement of untranslated sequences.…”
Section: Discussionmentioning
confidence: 69%
“…Earlier testing of SF1m and the related vector, SF-MDR, in various immortal as well as primary murine and human hematopoietic cells revealed that MDR1 expression from single copy integrations of this vector protected cells from the toxicity of high doses of PAC, COL or vincristine (2-3x the IC50) in vitro. 23,24,27,28 The control vector was SF1␦, 24 a retroviral gene marking vector encoding the cytoplasmically deleted nerve growth factor receptor (⌬NGFR). Both vectors had similar titers (5ϫ10 5 to 1ϫ10 5 infectious units/ml cell culture supernatant) in the amphotropic producer clones used here.…”
Section: Experimental Procedures To Evaluate Toxicity Of Paclitaxel (Pmentioning
confidence: 99%
“…In brief, about 500 Jurkat cells were plated per dish in 1.2 ml Iscove's modified MDM (Gibco BRL) containing 0.80% Methocult H4100 (Stem Cell Technologies, Remagen, Germany), 30% FCS (PAA), 1% BSA (Boehringer Mannheim), 10 −4 M mercaptoethanol (Merck), and 4 m M glutamine (Gibco BRL). After 10–12 d colonies were counted, randomly picked, washed and lysed as previously described ( Eckert et al , 1996 ). One tenth of the lysate was subjected to a nested PCR in an UNO thermocycler (Biometra, Göttingen, Germany) for detection of retroviral tk sequences using Goldstar Taq polymerase (Eurogentec, Seraing, Belgium).…”
Section: Methodsmentioning
confidence: 99%
“…The resulting amplification product was 404 bp long. Negative colonies were analysed for the presence of amplifiable genomic DNA using primers specific for the human haemopoietic cell kinase (HCK) gene essentially as described ( Eckert et al , 1996 ).…”
Section: Methodsmentioning
confidence: 99%
“…Retrovirus vector containing human mdr1 cDNA (SF-MDR) was kindly provided by C. Baum. 5 The vector was packaged in an amphotropic packaging cell line PA317. The titer of the virus was 2 × 10 5 cfu/ml and 2 × 10 4 cfu/ml when NIH3T3 cells and K562 cells were used as target cells of titering, respectively.…”
Section: Methodsmentioning
confidence: 99%